2020
DOI: 10.1002/bjs.11422
|View full text |Cite
|
Sign up to set email alerts
|

Safety of hospital discharge before return of bowel function after elective colorectal surgery

Abstract: Background Ileus is common after colorectal surgery and is associated with an increased risk of postoperative complications. Identifying features of normal bowel recovery and the appropriateness for hospital discharge is challenging. This study explored the safety of hospital discharge before the return of bowel function. Methods A prospective, multicentre cohort study was undertaken across an international collaborative network. Adult patients undergoing elective colorectal resection between January and April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…However, when evaluating our early discharge group, results show no significant difference in outcomes between those who had full return of gastrointestinal function and those who did not. In a recent large multicenter prospective study, discharge prior to return of bowel function was found to be safe in selected patients undergoing elective colorectal surgery [ 3 ]. These results suggest that discharge prior to recovery of gastrointestinal function is safe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when evaluating our early discharge group, results show no significant difference in outcomes between those who had full return of gastrointestinal function and those who did not. In a recent large multicenter prospective study, discharge prior to return of bowel function was found to be safe in selected patients undergoing elective colorectal surgery [ 3 ]. These results suggest that discharge prior to recovery of gastrointestinal function is safe.…”
Section: Discussionmentioning
confidence: 99%
“…However, most ERPs heavily rely on the return of gastrointestinal function as a necessary criteria for discharge [ 2 ]. Furthermore, there is emerging evidence that discharge prior to full gastrointestinal recovery within an ERP may be safe in selected patients and has not been associated with increased morbidity [ 3 ]. Considering these findings, recent studies have been successful in implementing same day discharge (SDD) protocols for minimally invasive colectomy in highly selected patients [ 4 , 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, complete laparoscopic excision with an anterior approach was performed as the treatment of choice, guaranteeing preservation of the pelvic plexus without entering the cysts and avoiding rectal injury. For upper abdominal tumors [21][22][23], minimally invasive surgery for retrorectal tumors allows safe resection of the tumor, reducing bleeding and injury [24], and improving recovery [25].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative ileus: absence of passage of gas or stools, and inability to tolerate oral intake or need for a nasogastric tube placement for more than 5 days. Recovery of bowel function will be assessed using the GI-2 method [15][16][17][18]: the sum of the first day of stool passage and the day on which a soft diet is started. A normal recovery is defined by achieving GI-2 within 10 days from surgery.…”
Section: Secondary Outcomesmentioning
confidence: 99%